Potential of C-Phenylcalix[4]Resorcinarene Epoxide Compound as Drug Delivery Agent in Breast Cancer Cells MCF-7 - Dwi Rahmasari Fatmawati; Danny Nur Wahyu Hidayat; Diah Kartika Sari; Rizky Riyami Putri; Jumina Jumina; Yehezkiel Steven Kurniawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Cancer therapy through conventional chemotherapy has been widely applied; however, one of the main disadvantages of chemotherapy is the non-selective targeting of cancer cells which causes various adverse side effects. The development of drug delivery agents that are more selective and effective in cancer therapy needs to be performed so that the drugs have a therapeutic effect and minimize side effects. In this study, the compound C-phenylcalyx[4]resorcinarene epoxide (CFKRE) has acted as a drug delivery agent because it can form host complex interactions with ligands. The CFKRE compound was synthesized through two reaction steps: the condensation and alkylation reactions of the epoxide. The structure was analyzed using FTIR, 1H-, and 13C-NMR spectrophotometers and then tested for in vitro cytotoxicity using the MTT assay. The results showed that 70% yield of CFKRE was obtained. Molecular docking analysis of CFKRE compounds against PDGFR and EGFR proteins showed high binding energy compared to conventional chemotherapeutic agents. Molecular dynamic studies showed that CFKRE compounds could form a host-ligand complex with a −350.4 kcal/mol binding energy. Cytotoxic assay of CFKRE compound against MCF-7 breast cancer cells and Vero cells gave IC50 values of 4.04 and 29.59 μg/mL, respectively. These results indicated that CFKRE compounds are not toxic and have the potential to be utilized as new candidates for drug delivery agents.